The Effect of Premium Income, Claim Payment, Risk-Based Capital, Investment Return, and Underwriting Result on the Profits of Insurance Companies Listed on the Indonesia Stock Exchange for the 2015- 2018 Period - Wahyono, W; Nurochim, N; Palupi, Indarti Diah (Riset Akuntansi dan Keuangan Indonesia, 2021)
This study aims to determine the effect of premium income, claim payment, risk-based capital, investment return, and underwriting result on the profit of insurance companies listed on the Indonesia Stock Exchange (IDX) for the 2015- 2018 period. The analysis techniques employed were panel data regression with the Common Effect Model, Fixed Effect Model, and Random Effect Model. The results of this study indicate that premium income, claim payment, and investment return have an effect on profits. Meanwhile, riskbased capital and underwriting result has no effect on profit.